Payback calculation system of introduction network solar power plants in private households - Гарячевська, Ірина Василівна; Іванющенко, Вікторія Віталіївна; Протектор, Денис Олегович (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2019)
The article describes the payback calculation system of introduction a network solar power plants in private households that are locating in Ukraine. The system takes into account such parameters as beam, ground-reflected and diffuse solar radiation with atmospheric attenuation, the angle and the orientation roof, the daily average temperature of photovoltaic cells and the temperature coefficient of solar panels, when calculating the generation of a network solar power plant. The flux of solar radiation that falls on the surface of the photovoltaic cells is determined of the Hay-Davis model. When calculating the payback solar power plant takes into account such parameters as annual electricity consumption, current electricity price, feed-in tariff and annual electricity price increase. The average market price of a network solar power plant is taken at the rate of 1 dollar per 1 watt of installed capacity. Based on these parameters, the system calculates a monthly, daily average and annual generation of a network solar power plant, calculates the relative cost of a network solar power plant, calculates of electricity costs forecast over twenty years and calculates a payback period of a network solar power plant. The monthly and daily average generation of a network solar power plant, electricity costs forecast over twenty years and payback period of a network solar power plant displayed in the system in the form of corresponding graphs and diagrams. In the case if investments necessary for the construction and commissioning of a network solar power plant don’t pay off within twenty years, the system will display this information in the corresponding field.